AAV-shDUX4 provides short-term benefits but limited long-term efficacy in a DUX4 mouse model of FSHD - S. Sohn; S. Reid; M. Bowen; C. Hudon; E. Corbex; B. Morel; C. Hourde; V. Mariot; J. Dumonceaux (Molecular Therapy: Methods & Clinical Development)
The aberrant expression of the toxic transcription factor DUX4 in skeletal muscle is a hallmark of facioscapulohumeral muscular dystrophy. Effective therapeutic strategies will likely require the inhibition of DUX4, with adeno-associated virus (AAV)-mediated therapies being among the promising approaches. However, the regenerative nature of muscle tissue can impact the long-term efficacy of AAV transduction, leading to reduced transgene persistence and diminishing the sustainability of gene inhibition over time. In this study, we utilized an AAV vector carrying a short hairpin RNA targeting DUX4 (shDUX4) to suppress DUX4 expression in the ACTA1-MCM; FLExDUX4/+ mouse model, which exhibits progressive muscular dystrophy. One month following AAV administration, the treatment significantly mitigated the DUX4-associated pathological features, including molecular, histopathological, and functional force-velocity-endurance (FoVE) parameters. However, by 10 months post-treatment, the therapeutic effects had substantially diminished, with most pathological markers remaining uncorrected and no sustained improvement in muscle force. This decline in therapeutic effect was associated with reduced DUX4 knockdown and a concurrent loss of AAV genomes. These findings highlight that although AAV-mediated gene therapy holds significant promise for FSHD treatment, challenges such as muscle fiber turnover and AAV genome dilution must be overcome to achieve sustained therapeutic benefit.